2003
DOI: 10.1128/jvi.77.12.6601-6612.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genome Replication, Virion Secretion, and e Antigen Expression of Naturally Occurring Hepatitis B Virus Core Promoter Mutants

Abstract: The core promoter mutants of hepatitis B virus (HBV) emerge as the dominant viral population at the late HBeAg and the anti-HBe stages of HBV infection, with the A1762T/G1764A substitutions as the hotspot mutations. The double core promoter mutations were found by many investigators to moderately enhance viral genome replication and reduce hepatitis B e antigen (HBeAg) expression. A much higher replication capacity was reported for a naturally occurring core promoter mutant implicated in the outbreak of fulmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
299
5
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(326 citation statements)
references
References 58 publications
19
299
5
3
Order By: Relevance
“…This double mutation induces an increased inflammatory response that becomes stronger as the progression of liver damage transits through chronic hepatitis and into a cirrhosis stage (34). The underlying mechanism of the effects of HBV antigen on the biology of inflammation and cirrhosis is still unclear, but there are substantial data that point to modulation of the immune surveillance system and immune tolerance in the presence and absence of this protein (33)(34)(35). The HBV 1762 T ͞1764 A double mutation also affects the amino acid sequence of the HBV X gene, because it resides in codons 130 and 131, thereby inducing lysine to methionine and valine to isoleucine alterations, respectively (36).…”
Section: Discussionmentioning
confidence: 99%
“…This double mutation induces an increased inflammatory response that becomes stronger as the progression of liver damage transits through chronic hepatitis and into a cirrhosis stage (34). The underlying mechanism of the effects of HBV antigen on the biology of inflammation and cirrhosis is still unclear, but there are substantial data that point to modulation of the immune surveillance system and immune tolerance in the presence and absence of this protein (33)(34)(35). The HBV 1762 T ͞1764 A double mutation also affects the amino acid sequence of the HBV X gene, because it resides in codons 130 and 131, thereby inducing lysine to methionine and valine to isoleucine alterations, respectively (36).…”
Section: Discussionmentioning
confidence: 99%
“…The 1762 T /1764 A double mutation has also been shown to affect an increase in the rate of HBV genome synthesis in cellular models (10,11). In cellular studies, the 1762 T /1764 A double mutation increased the replication of the viral genome 2-fold; in the case of some of the rarer triple mutations detected in this investigation, an 8-fold increase in genome replication was found (10,37). Thus, the alterations that we have detected in our study subjects before liver cancer diagnosis may be selective toward the eventual development of the disease.…”
Section: Discussionmentioning
confidence: 62%
“…This double mutation tracks with an increased inflammatory response that becomes stronger as the progression of liver damage transits through chronic hepatitis and into a cirrhosis stage (36). The underlying mechanism of the effects of HBV e antigen on the biology of inflammation and cirrhosis is still unclear, but there are substantial data that point to modulation of the immune surveillance system and immune tolerance in the presence and absence of this protein (31,36,37). The 1762 T /1764 A double mutation has also been shown to affect an increase in the rate of HBV genome synthesis in cellular models (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that both HBV DNA and the antigens were expressed in the transfected cells, but not in the negative control cells transfected with pcDNA3.1 (+). As shown in Table 1 [29] . In addition, HBV DNA expression levels of each of the recombination plasmids were ≥ 10 8 copies/mL in HepG2 cells (Table 2), which indicates that the three recombinant plasmids can be expressed efficiently.…”
Section: Discussionmentioning
confidence: 76%